A round-trip contrast: Israel and Venezuela from 1987 to 2012. - M. Febres, Laura (Historia y Comunicación Social, 2014)
In the following work, we will describe two different moments of the female story that has been generated between the Israeli and Venezuelan communities. As a proof of that, we will analyze the novel Cláper by Alicia Freilich (1987) in which the author narrates the arrival of her father to Venezuelan soil coming from Léndov, Poland. At first, the father lives alone, but then he raises a family that lives throughout different historic times of Venezuela, from the dictatorship of Juan Vicente Gómez to the sudden appearance of the guerrillas in the national panorama. The novel is narrated by the daughter, who despite the lack of instruction of her parents, is able to attend university disobeying her father’s warnings of not following the way to which that education could lead her. The study of this first novel holds the merit of revealing the intimacy of a family in which we can observe the father’s responsible behavior to his wife and children in contrast to other novels where the women are physically abused even by those who call themselves “liberals”. The second story can be found in the book Pasaje de Ida (2012) compiled by the writer Silda Cordoliani in which the Venezuelan writer Liliana Lara expresses in a photography-like story her experiences in Israel, a country where she has recently emigrated. It is also possible to read about all the setbacks of a family that has to adapt to a new lifestyle.
Keywords: story; 20th and 21st centuries; Venezuela; Israel.